Characteristics of recently arrived Asian men who have sex with men diagnosed with HIV through sexual health services in Melbourne and Sydney. (9th July 2019) - Blackshaw, Lucinda C.D.; Chow, Eric P.F.; Varma, Rick; Healey, Loretta; Templeton, David J.; Basu, Ashna; Turner, Dane; Medland, Nick A.; Rix, Suzanne; Fairley, Christopher K.; Chen, Marcus Y.
Abstract: Objectives: Asian men who have sex with men (MSM) who have recently arrived in Australia are an emergent risk group for HIV; however, little is known about how they compare to Australian MSM diagnosed with HIV. This study compared the characteristics of these two groups. Methods: A retrospective, cross‐sectional study of MSM diagnosed with HIV between January 2014 and October 2017 in Melbourne and Sydney public sexual health clinics. Asian MSM were those who had arrived in Australia within 4 years of diagnosis. Results: Among 111 Asian men, 75% spoke a language other than English, 88% did not have Medicare and 61% were international students. Compared with Australian men (n=209), Asian men reported fewer male sexual partners within 12 months (median 4 versus 10, p <0.001), were less likely to have tested for HIV previously (71% versus 89%, p <0.001) and had a lower median CD4 count (326 versus 520, p <0.001). Among Asian men, HIV subtype CRF01‐AE was more common (55% versus 16%, p <0.001) and subtype B less common (29% versus 73%, p <0.001). Conclusions: Asian MSM diagnosed with HIV reported lower risk and had more advanced HIV. Implications for public health: HIV testing and preventative interventions supporting international students are required.